A Little Less Conversation? Track II Dialogue and Transboundary Water Governance. Issue 2 (11th May 2017) - Hanasz, Paula
Abstract: Foreign aid donors are increasingly investing in the good governance of freshwater resources in developing countries. One method used by many such programs is Track II Dialogue—informal discussions between government and non‐government stakeholders facilitated by a neutral third party. There are many merits to participatory and discursive governance; however, there are also some limitations. This article considers the advantages and disadvantages of Track II Dialogue in transboundary water governance. It examines the relationship between discursive governance and water justice and analyses the role of the neutral third party facilitator. It also considers to what extent trust and cooperation must be present between riparians for deliberative processes to succeed. These observations are based on an analysis of foreign‐led initiatives in the Ganges‐Brahmaputra‐Meghna basin. Foremost among these is the World Bank‐funded South Asia Water Initiative, which aims to improve cooperation between riparian states by facilitating Track II Dialogue.